UPAYA PEMEKARAN PROVINSI KEPULAUAN NIAS (STUDI KEPENTINGAN ELITE POLITIK) - Zebua, Ben Hansel N.; Tinov, M. Y. Tiyas (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The effort process of retransformation of Nias Islands Province is started from the political elite’s idea. In its development, the political elite with every attribute they have (especially the political elite in local/regional level) have an influence and strong role in the regional autonomy era nowadays. The purpose of this research is to know the dynamics of the effort process of retransformation of Nias Islands Province in its relation with the interest of political-government elite and non-government political elite in local level and the factors that influences the effort process of retransformation of Nias Islands Province. Research method that used is qualitative research method and the analysis descriptive approach and use interview and documentation to collect the data. The used theory in this research is regional autonomy, retransformational area conception, and elite theory.Based on the empirical research, it has been found the fact that the dynamics that take place from 2009 until 2014 look so difficult. Began with the declaration of establishment Nias Islands Province from 2009 until in 2014 as the year that signed with the postponement of legalization of the establishment the new autonomous area Nias Islands Province. Besides that, the existence of interrelation of interest interpolitical elite also describes the answers of political elites toward the effort process of retransformation of Nias Islands Province that consists of two points these are economical interest and political interest. The factors that influence the effort process of retransformation of Nias Islands Province consist of supporting factor that is the involvement of political elite and inhibiting factors these are the internal dynamics of political elite, the moratorium of establishment of DOB (new autonomous area), and the mechanism of law 23 year 2014 about regional governance. In this research, the author concludes that there is a difficult dynamics that take place chronologically from 2009 as the first year of declaration the establishment of Nias Islands Province until the difficult struggle until the process of plenary session in The House of People’s Representative of Indonesia at 2014 that postponed the legalization of the establishment of Nias Island Province considering the change of government regime and the change of Indonesian Parliamentary period from 2009-2014 to 2014-2019 period.Keywords: Political elite, interest, and the establishment of Nias Islands Province